ANALYSIS OF THE EFFECT OF SEA BREEZE ON THE DISTRIBUTION OF PM10 EMISSIONS USING WRF CALPUFF MODEL (CASE STUDY: PT. PERTAMINA RU IV CILACAP) - Rosyidatunnajah, Suci
Oil processing activities at PT. Pertamina RU IV Cilacap produce various hazardous gas emissions, including PM10. The proximity of the refinery to residential areas increases the risk of PM10 exposure for the surrounding community. Additionally, the refinery's location near the sea creates the potential for sea breezes to influence the distribution of pollutants. This study aims to determine the impact of sea breezes on the distribution of PM10 emissions originating from PT. Pertamina RU IV Cilacap. In this research, study days were selected using meteorological observation data and ERA5 Reanalysis data. On the selected study days, the WRF model was used to simulate sea breezes. Subsequently, the CALPUFF model was employed using PM10 emission data, chimney physical data, topographic data, land cover data, and meteorological data generated by the WRF model to evaluate the distribution of PM10 emissions during sea breeze conditions. The simulation results indicate that the area around PT. Pertamina RU IV Cilacap is influenced by sea breeze during the day. This sea breeze causes PM10 emissions to disperse inland, predominantly affecting residential and agricultural areas. The highest concentration of dispersed PM10 during the sea breeze ranges from 5.7 µg/m³ to 14.72 µg/m³. This concentration level is still considered good according to the Air Pollution Standard Index (ISPU) and, therefore, does not pose a risk to human health.